Relationship between solar wind parameters and geomagnetic activity indices / Azrin Nur Farhana Abdullah Din @ Azman - Abdullah Din @ Azman, Azrin Nur Farhana (2014)
This study examined the relationship of solar wind parameters due to geomagnetic activity indices during disturbed period (Coronal Holes events & Coronal Mass Ejection events) and quiet period. In this analysis, for solar wind parameters, we are focusing on Interplanetary Magnetic Field Magnitude (B), Interplanetary Magnetic Field Temperature (T), Proton Density (N), Solar Wind Speed (Vsw) and Solar Wind Input Energy (e) while for the geomagnetic indices, polar cap index (PC), auroral electrojet index (AE), disturbance storm time index (Dst) and planetary K-index (Kp) were investigated. The solar wind parameters and geomagnetic indices data are retrieved from OMNIWeb Data Explorer maintained by Goddard Space Flight Center, NASA. The variability of horizontal component of the geomagnetic field at three different latitudes stations extracted from Magnetic Data Acquisition System/Circum-pan Pacific Magnetometer Network (MAGDAS/CPMN) were investigated in order to study the correlation of geomagnetic pulsations with solar wind parameters. Data are supplied by International Center for Space Weather Science and Education, ICSWSE, Kyushu University, Japan. Due to availability of data, the event within 2009 and 2010 period were chosen. From the analysis, both Coronal Holes and Coronal Mass Ejection events show significant relationship with geomagnetic indices and pulsations. Both solar wind events influence the geomagnetic pulsations according to the geomagnetic stations. Details of the analysis will be discussed throughout this paper.